Nutritional Constraints of Rice -Legume System in Laterite Soils of Humid Tropics - Gracy Mathew (Department of Agronomy, College of Horticulture, 2002)
A research programme entitled "Nutritional constraints of rice- legume system in laterite soils of humid tropics" was carried out from 1997-'98 to'1999- '00 at Regional Agricultural Research Station, Pattambi. The objectives of the programme were to study the effect of crop residue recycling, nutrient management practices and tillage and water management practices on soil and plant elemental status and productivity of rice- rice-legume cropping system There were two experiments in the programme. The first experiment entitled, "Soil- plant elemental status and productivity as influenced by crop residue recycling and nutrient supply in the rice-legume cropping system" was taken up to study the impact of nutrient management practices as well as crop residue recycling on soil productivity and crop growth. The crop residues added in the system involved harvested left overs of grain cowpea crop during summer as well as addition of two-third portion of straw of kharif crop to rabi season crop. Silica at 250 kg ha", higher K dose of 70 kg ha-I and soiVfoliar supply of Mg, Zn, Cu, B and Mo were also included in various treatment combinations. The treatments exhibited significant influence on grain and straw yield. The treatment which did not receive any inorganic fertilizers registered the lowest yield during all the seasons. Straw addition did not' bring about yield advantage in kharif, but in rabi there was steady and significant increase over the seasons. Silica application was not beneficial in initial seasons, but from fourth rice crop onwards, significant increase was noticed. Though there was an improvement in organic carbon of soil during some seasons, summer cowpea raising did not bring about specific yield improvement. The absence of response to addition of summer cowpea residues revealed that either lack of N or a lower level of organic carbon may not be the limiting factors for low yield in these laterite soils. Potassium application even at the higher dose of 70 kg ha-I was "found to have no appreciable effect on growth and yield of paddy. Foliar application of